ADDITION OF SUGARCANE BAGASSE FOR THE PRODUCTION OF PARTICLEBOARDS BONDED WITH UREA-FORMALDEHYDE AND POLYURETHANE RESINS - Soler Cunha Buzo, Ana Laura; Mello Silva, Sergio Augusto [UNESP]; De Moura Aquino, Vinicius Borges; Chahud, Eduardo; Melgaco Nunes Branco, Luiz Antonio; De Almeida, Diego Henrique; Christoforo, Andre Luis; Boff Almeida, Joao Paulo; Rocco Lahr, Francisco Antonio (Slovak Forest Products Research Inst, 2020)
The present study deals with a production of pine particleboards using the sugarcane bagasse content and using castor-oil based bicomponent polyurethane resin and urea-formaldehyde resin. The influence of incorporation of sugarcane bagasse on the physical and mechanical properties of the composites was evaluated. The particleboards were produced according Brazilian standard ABNT NBR 14810, but performance requirements have been analyzed using Brazilian and international standards, as well. Treatment 2, using PU resin, were considered the best treatment using pine residue and sugarcane bagasse, presenting physical properties values 60% lower and mechanical properties 65% higher on average when compared with panel without sugarcane bagasse, indicating the good performance of sugarcane incorporation and the possibility of its use on commercial purpose for thermal and acoustic insulation. The addition of sugarcane bagasse improved physical and mechanical properties of particleboards when compared to panels manufactured from pine wood particles only. Statistical analysis indicated that moisture content and bagasse content were significant, enhancing properties when compared with reference treatments.
Keywords: Pinus sp.; sugarcane bagasse; particleboards; urea-formaldehyde; polyurethane resin; castor oil